Diversity of bartonellae in mites (Acari: Mesostigmata: Macronyssidae and Spinturnicidae) of boreal forest bats: Association of host specificity of mites and habitat selection of hosts with vector potential - Sándor, Attila D.; Corduneanu, Alexandra; Orlova, Maria; Hornok, Sándor; Cabezas‐Cruz, Alejandro; Foucault‐Simonin, Angélique; Kulisz, Joanna; Zając, Zbigniew; Borzan, Mihai (Medical and veterinary entomology, 2024)
Research into various bacterial pathogens that can be transmitted between different animals and may have zoonotic potential has led to the discovery of different strains of Bartonella sp. in bats and their associated ectoparasites. Despite their enormous species diversity, only a few studies have focussed on the detection of bacterial pathogens in insectivorous bats of boreal forests and their associated Macronyssidae and Spinturnicidae mites. We collected and molecularly analysed mite samples from forest‐dwelling bat species distributed all along the boreal belt of the Palearctic, from Central Europe to Far East. Ectoparasitic mites were pooled for DNA extraction and DNA amplification polymerase chain reaction (PCRs) were conducted to detect the presence of various bacterial (Anaplasmataceae, Bartonella sp., Rickettsia sp., Mycoplasma sp.) and protozoal (Hepatozoon sp.) pathogens. Bartonella sp. DNA was detected in four different mite species (Macronyssidae: Steatonyssus periblepharus and Spinturnicidae: Spinturnix acuminata, Sp. myoti and Sp. mystacinus), with different prevalences of the targeted gene (gltA, 16‐23S ribosomal RNA intergenic spacer and ftsZ). Larger pools (>5 samples pooled) were more likely to harbour Bartonella sp. DNA, than smaller ones. In addition, cave‐dwelling bat hosts and host generalist mite species are more associated with Bartonella spp. presence. Spinturnicidae mites may transmit several distinct Bartonella strains, which cluster phylogenetically close to Bartonella species known to cause diseases in humans and livestock. Mites with ubiquitous presence may facilitate the long‐term maintenance (and even local recurrence) of Bartonella‐infestations inside local bat populations, thus acting as continuous reservoirs for Bartonella spp in bats. Bats play a major role in the circulation of zoonotic pathogens. Mites (Macronyssidae and Spinturnicidae) may facilitate the long‐term maintenance (and even local recurrence) of Bartonella‐infestations. Mites may transmit several distinct Bartonella strains, which cluster phylogenetically close to Bartonella species known for their zoonotic role.